Unveiling the Dynamics of Tax Compliance: The Implementation and Challenges of the Directorate General of Tax - Liyonna, Sherin Amirtha; Suaidah, Imarotus; Srihastuti, Eni (Economics, Business, Accounting & Society Review, 2026)
Contemporary tax compliance research has increasingly shifted from deterrence-based models toward behavioral frameworks that emphasize psychological, social, and institutional determinants of voluntary compliance. Despite advances in digital tax administration, compliance rates in many developing contexts remain volatile, suggesting that technological modernization alone is insufficient to transform taxpayer behavior. Drawing on the Theory of Planned Behavior (TPB), this study examines how attitudes, subjective norms, and perceived behavioral control interact to shape taxpayers’ compliance intentions and behaviors within the policy implementation context of the Directorate General of Taxes (DGT) in Kediri, Indonesia. Employing a qualitative case study design, data were collected through in-depth interviews with tax officials, individual and corporate taxpayers, and MSME association representatives, complemented by observations and document analysis. The findings reveal that positive compliance intentions emerge from perceived fiscal transparency, reputational pressures within business networks, and improved access to administrative support; however, a persistent intention–behavior gap remains when digital literacy constraints and financial stress undermine perceived behavioral control. The study demonstrates that trust-based compliance requires an integrated intervention framework that simultaneously strengthens institutional legitimacy, social norms, and operational capacity. Theoretically, this research extends TPB by contextualizing its constructs within institutional transformation from sanction-based to trust-based governance. Practically, it provides evidence-based policy recommendations for enhancing long-term voluntary compliance in decentralized tax administrations.